Monitoring EDTA and endogenous metabolite biomarkers from serum with mass spectrometry. Issue 3 (2005) - Lowe Lowe, Rachel Rachel; Go Go, Eden P. Eden P.; Tong Tong, Grace C. Grace C.; Voelcker Voelcker, Nicolas H. Nicolas H.; Siuzdak Siuzdak, Gary Gary
Abstract : We describe a quantitative method for the determination of ethylenediaminetetraacetic acid (EDTA) in human serum by gas chromatography mass spectrometry (GC-MS), liquid chromatography electrospray ionisation tandem mass spectrometry (LC-ESI-MS/MS), and desorption ionisation on silicon mass spectrometry (DIOS-MS). In the initial stages of the analysis, endogenous metabolites (1-palmitoyl-sn-glycero-3-phosphocholine and 1-stearoyl-sn-glycero-3-phosphocholine) were readily observed in LC-ESI-MS and DIOS-MS however, direct analysis of the EDTA free acid had limited sensitivity. In order to improve EDTA detection we employed a straightforward esterification derivatization. The most successful derivatization procedure converted EDTA to its methyl ester and, since 13 C isotopes of these reagents are readily available, internal standards could be easily generated for quantitative analysis. This approach provided a limit of detection of 0.5 and 0.1 μM for GC-MS and LC-ESI-MS, and offers a viable method for the EDTA detection.